(untitled) (EduVision: Journal of Innovations in Pedagogy and Educational Advancements, 2025)
This article provides detailed information about the activities of the “El-yurt umidi” Foundation of Uzbekistan, its role in providing young people with opportunities to study at foreign higher educational institutions, and the Foundation’s contribution to the country’s economic and social development. The text describes the conditions created for talented young people to study at leading universities in the world through scholarship programs and competitions organized by the Foundation since 2018. Through this, the goal is to provide young people with modern knowledge, train competitive personnel, and contribute to the economic development of Uzbekistan. In particular, it shows how to use the experience of young specialists who have studied abroad for economic and scientific growth in the country.